Implementation of the Use of Quick Response Code Indonesian Standard (QRIS) In Fraud Prevention: (Case Study of Kuala Alam BUMDes and Sebauk BUMDes) - Nadila, Cahaya Putri; Muttaqin, Husnul (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research is motivated by the implementation of QRIS in Village-Owned Enterprises (BUMDes), which continues to be encouraged through the village financial digitalization program. Although QRIS is designed to be secure, field practices show that fraud can still occur when internal controls are weak. The novelty of this study lies in its analysis of QRIS-related fraud in BUMDes, an area that has not been widely examined, as well as in the evaluation of its compliance with PADG 21/18/2019. This research aims to describe the implementation of QRIS in BUMDes Kuala Alam and BUMDes Sebauk, and to identify potential fraud, operational challenges, and the effectiveness of regulations as fraud prevention measures. The study employs a qualitative method through interviews, observations, and documentation. The results indicate that BUMDes Sebauk implements QRIS in accordance with the regulations, resulting in a low fraud risk, while BUMDes Kuala Alam still has potential fraud risks due to the use of personal QRIS and weak verification procedures. Two fraud indications were found: fund discrepancies and fake transfer proofs. QRIS regulations are adequate, but their effectiveness heavily depends on the internal controls of each BUMDes.